2021
DOI: 10.3906/yer-2004-20
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent model for earthquake occurrence and effects of design spectra on structural performance: a case study from the North Anatolian Fault Zone, Turkey

Abstract: We have investigated the time-dependent seismicity model of the earthquake occurrence on a regional basis through the North Anatolian Fault Zone (NAFZ). To that end, the studied region has been subdivided into 7 seismogenic zones considering the seismotectonic criteria, and then regional time and magnitude predictable (RTIMAP) model has been performed. Intervened times and magnitudes of main shocks produced in each zone have predictive properties defined by the RTIMAP. The probabilities of the next main shocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 64 publications
0
3
0
2
Order By: Relevance
“…Turkish Earthquake Hazard Map Interactive Web Application (TEHMIWA) has become available for the computation of earthquake parameters used in structural analyses for any geographic location since the beginning of 2019 [68][69][70][71][72][73]. The comparison of the peak ground acceleration (PGA) and peak ground velocity (PGV) values in fifteen ReMi measurement locations considered within the scope of the study for all earthquake ground motion levels are shown in Table 1 through the TEHMIWA.…”
Section: Resultsmentioning
confidence: 99%
“…Turkish Earthquake Hazard Map Interactive Web Application (TEHMIWA) has become available for the computation of earthquake parameters used in structural analyses for any geographic location since the beginning of 2019 [68][69][70][71][72][73]. The comparison of the peak ground acceleration (PGA) and peak ground velocity (PGV) values in fifteen ReMi measurement locations considered within the scope of the study for all earthquake ground motion levels are shown in Table 1 through the TEHMIWA.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that December 27, 1939, Erzincan, December 20, 1942, Niksar-Erbaa, June 20, 1943, Adapazari-Hendek, November 26, 1943, Tosya-Ladik and February 1, 1944, Bolu-Gerede earthquakes occurred at close time intervals and led to huge economic losses and casualties triggered the efforts to reduce earthquake losses in Turkey [81,82]. Turkey's first official earthquake zonation map was prepared in 1945 following these earthquakes [83,84].…”
Section: Current Seismic Parameters Of Bitlismentioning
confidence: 99%
“…Bu çalışmalarda farklı yapı tipleri için deprem kuvveti hesap yöntemleri, taban kesme kuvvetleri, deplasmanlar, periyot, hedef deplasmanlar, katlar arası ötelenmeler, spektrum eğrileri ve kesit hasar değerleri incelenmiştir. [10][11][12][13][14][15][16][17] Karasin vd. [18] çalışmalarında coğrafi konuma özel tasarım spektrumlarının betonarme yapı performansına etkisini incelemişleridir.…”
Section: Introductionunclassified